2019
DOI: 10.1002/adfm.201808967
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Mechanotransduction in Three Dimensions using Sub‐Cellular Scale, Crosslinkable Fibers of Controlled Diameter, Stiffness, and Alignment

Abstract: The extracellular matrix (ECM) is a complex, three-dimensional (3D) framework of macromolecules, which regulate cell bioactivities via chemical and physical properties. The ECM's physical properties, including stiffness and physical constraints to cell shape, regulate actomyosin cytoskeleton contractions, which induce signaling cascades influencing gene expressions and cell fates. Engineering such bioactivities, a.k.a., mechanotransduction, have been mainly achieved by two-dimensional (2D) platforms, such as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 47 publications
4
18
0
Order By: Relevance
“…Whereas FAs adopted a spindle shape on the 2D TCP, our data showed that 3D FAs were round-shaped (Figure 2a) and were mainly located in the vicinity of optus angles between the PLC fibers, which is consistent with data from 2D micropatterning [44]. Fewer FAs numbers (Figure 2b) and elongated nucleus (Figure 2a) were detected in the aligned PCL porous membranes, given that the cell and nucleus need to accommodate the change in cell shape, which is in accordance with cell shape in aligned nano-PCL fibers [22,44,45]. It is worth noting that cells may interact with multiple fibers at the corner of the PCL-A scaffold, while most of the cells might adhere to a single fiber in the PCL-A group with less surface area than random fibers where cells can interact with more than one fiber.…”
Section: Focal Adhesions Are Altered On Aligned Fibers On a Pcl Porous Scaffoldsupporting
confidence: 81%
See 1 more Smart Citation
“…Whereas FAs adopted a spindle shape on the 2D TCP, our data showed that 3D FAs were round-shaped (Figure 2a) and were mainly located in the vicinity of optus angles between the PLC fibers, which is consistent with data from 2D micropatterning [44]. Fewer FAs numbers (Figure 2b) and elongated nucleus (Figure 2a) were detected in the aligned PCL porous membranes, given that the cell and nucleus need to accommodate the change in cell shape, which is in accordance with cell shape in aligned nano-PCL fibers [22,44,45]. It is worth noting that cells may interact with multiple fibers at the corner of the PCL-A scaffold, while most of the cells might adhere to a single fiber in the PCL-A group with less surface area than random fibers where cells can interact with more than one fiber.…”
Section: Focal Adhesions Are Altered On Aligned Fibers On a Pcl Porous Scaffoldsupporting
confidence: 81%
“…Our data demonstrate that LAMIN A/C was detected in both 2D and 3D, although the aligned fibers led to an elongated nucleus with enhanced LAMIN A/C fluorescence (Figure 3a). YAP is a known key mechanotransductive transcription factor that contributes to the retention storage of the mechanical 'memory' of past cell-matrix interactions [11]; our previous research showed that in 2D substrates, higher vinculin expression led to higher nuclear YAP accumulation and nuclear mechanical tension at an early point (24 h) and was associated with increased osteogenic differentiation in human mesenchymal stem cells [8,45]. LAMIN A/C and YAP were stained for hOBs on the 3D porous scaffolds and TCP (Figure 3).…”
Section: The Effect Of Fiber Alignment On Nucleus Mechanosensingmentioning
confidence: 99%
“…An important issue related to decellularized tissues is biomechanical behavior. In general, it is well known that the biomechanical properties of tissues are important variables affecting tissue function and cell mechanotransduction [50]. However, the decellularization process may significantly alter the structure of the tissue ECM and, thus, the biomechanical properties of the decellularized scaffolds, which could alter the phenotype, proliferation capability, and differentiation potential of the cells cultured on this scaffold and modify cell behavior and tissue regeneration [51].…”
Section: Discussionmentioning
confidence: 99%
“…8). Alternative fiber systems that allow for cell encapsulation exist, but they employ rigid polymers that cells cannot remodel (19,20), are composites with extensible fibers embedded in a continuous gel phase that limits fiber recruitment (28), or are on scales that are much larger than single cells (22,23). To engage cell adhesion through integrins, fibrous assemblies are decorated with a peptide containing the adhesive RGD motif for all cell studies.…”
Section: Cell-mediated Fiber Recruitment and Contractility Of Fibrous Hydrogel Assembliesmentioning
confidence: 99%
“…Although these gels permit cell encapsulation, their nano-scale porosity limits cell mobility and it is unclear if cells can contract these materials similar to natural ECM (14). Micro-to-nano scale fibrous materials that permit cell encapsulation and have diameters within the range of ECM fibers (14) have been described; however, the materials used in these systems are highly rigid, providing fibers that cells cannot physically remodel (19,20). Another important material is formed by electrospinning hydrogel fibers with moduli similar to natural ECM that allow cells to contract and compact fibers in a manner similar to collagen contraction; (21) yet, these electrospun scaffolds are rather stiff pre-formed solids that are not amenable to cell encapsulation or injection.…”
Section: Introductionmentioning
confidence: 99%